1992
DOI: 10.1007/bf00788951
|View full text |Cite
|
Sign up to set email alerts
|

The Sydney intervention trial: a controlled trial of relatives' counselling to reduce schizophrenic relapse

Abstract: The result of a psychosocial intervention which aimed to reduce schizophrenic relapse through relatives' counselling is presented. Thirty-six schizophrenic patients living in high Expressed Emotion (EE) parental households were randomly allocated to an intervention or control group. The parents of patients allocated to the intervention were offered ten weekly sessions of counselling. The patient was not included in these sessions. Patients in both groups received standard after-care of medication and support. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 23 publications
0
45
1
3
Order By: Relevance
“…However, this effect was vitiated when interventions involving multiple family groups were included. Four studies (Goldstein et al 1978 ;Leff et al 1982 ;Tarrier et al 1988 ;Vaughan et al 1992) provided data on relapses recorded up to 15 months after the end of treatment. There was no evidence for any beneficial effects of single family interventions on the likelihood of relapsing at the follow-up stage.…”
Section: Relapsementioning
confidence: 99%
See 2 more Smart Citations
“…However, this effect was vitiated when interventions involving multiple family groups were included. Four studies (Goldstein et al 1978 ;Leff et al 1982 ;Tarrier et al 1988 ;Vaughan et al 1992) provided data on relapses recorded up to 15 months after the end of treatment. There was no evidence for any beneficial effects of single family interventions on the likelihood of relapsing at the follow-up stage.…”
Section: Relapsementioning
confidence: 99%
“…Four studies (Posner et al 1992 ;Vaughan et al 1992 ;Bloch et al 1995 ;Buchkremer et al 1995) provided follow-up information on readmission rates up to 2 years after the end of treatment, but they showed no advantage for family interventions.…”
Section: Readmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data of Spiegel and Wissler (24) showed that while family consultation in the home for recently discharged schizophrenic patients did not prevent readmission, it did provide a significant decrease in time spent in the hospital for the first 3 months. The only study that did not demonstrate a statistically significant difference between a family treatment group and a control group was the one conducted by Vaughan et al (28), where a briefer intervention of counseling for the patient's relative was used in lieu of family therapy, which generally involves the patient as part of the process. In reviewing successful family treatments in other studies as compared with their own, Vaughan et al concluded that both the inclusion of the patient in the family treatment and the longer course of family treatment in the other studies appeared to lead to significantly better results.…”
Section: Clinical Trials With Random Assignment Of Subjectsmentioning
confidence: 99%
“…Likewise, the spacing of treatments ranges from weekly (e.g. Falloon et al, 1982;Vaughan et al, 1992) to a session every month (or even 3 months - Zhang et al, 1994). This range of intensity obviously blurs the distinctions between treatment and post-treatment booster sessions.…”
Section: Epidemiologia E Psichiatriamentioning
confidence: 99%